Análise de viabilidade técnica e econômica para implantação de aerogerador para propriedades rurais de Cascavel, Londrina e Palmas-PR - Gnoatto, Henrique (2017)
The World nations want to supplement their energy matrixes by using cleaner energy sources. This fact is justified because of the environmental impacts of the traditional forms of power generation, as well as the search for new energy sources. Brazil has natural resources conducive to the holding of clean energy, such as wind. The increase in the consumption and the growing political and environmental pressure to sustainable development, has made the energy matrixes planning more strict on the use of alternative energy sources. The work consists in the study of technical and economic viability for the implementation of wind turbines in rural properties in the cities of Cascavel, Londrina and Palmas, all located in the state of Paraná. Wind direction and velocity data collected by SIMEPAR were used from January 1, 2011 to December 30, 2015. The Weibull distribution was chosen as a probabilistic statistical model to represent the wind behavior in the localities. The study regions were chosen due to the geographic location and three models of rural properties were defined, taking into account the daily consumption of electric energy. The implantation of aerogenerators was technically feasible in the rural properties of the cities of Cascavel and Palmas, and not feasible in the rural properties of Londrina. However, all research scenarios were considered economically unviable.